Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) dalam Meningkatkan Efisiensi Pelayanan - Didit Setiawan; Achmad Fauzan Rachman (Journal of Educational Innovation and Public Health, 2026)
The implementation of Hospital Management Information Systems (HMIS) has become a strategic imperative to enhance operational efficiency amidst the ongoing global digital health transformation era. This study aims to analyze the determinants of successful HMIS implementation and its impact on service efficiency and patient outcome quality. Employing a narrative review approach with thematic synthesis of literature from PubMed, Scopus, and ScienceDirect databases between 2016-2026, the study evaluates the relationship between technology investment and organizational performance. The synthesis results indicate that while HMIS significantly reduces administrative burdens and medication errors, a "digital paradox" exists where technical efficiency may disrupt interpersonal interactions between healthcare providers and patients if systems are not user-centered. Key success factors include data interoperability (HL7/FHIR standards), human resource readiness, and governance policy support. This study concludes that a patient-centered efficiency model is the fundamental basis for ensuring technology investments yield sustainable added value within the healthcare delivery system.